Let public enjoy forest - The Star, Farida Shah (2012)
IWISH to refer to the article on the Ayer Hitam Forest Reserve (The Star, June 9). It was stated that this forest reserve is rich in biodiversity and serves as an outdoor research lab for undergraduates specialising in forest research, and therefore it is off limits to the public. The l,176ha forest was gazetted as an education and research forest.